THE CORRELATIONS AMONG CONSTRUCTS IN THE HEALTH BELIEF MODEL AND SELF-EFFICACY IN APPLYING THE NEWLY DEVELOPED INDONESIAN MODEL OF ASSERTIVE COMMUNICATION (CERDAS) - Puspitawati, Theresia; Prabandari, Yayi Suryo; Sastrowijoto, Soenarto; Paramastri, Ira; Claramita, Mora (Public Health of Indonesia, 2018)
Background: One of the most important factors in providing health services is communication. Effective communication between patient-physician will have an impact on health outcomes. Nevertheless, a gap still occurs in patient-physician communication.Objective: This study aimed to determine the correlation between the core concepts of the well-established Health Belief Model: perceived susceptibility, perceived severity, perceived benefits, perceived barriers and cues to action with the concept of self-efficacy in applying the newly developed Indonesian Model of Assertive Communication called "CERDAS”.Methods: A cross sectional study was conducted with 202 eligible women of the Family Welfare Programme in Yogyakarta, Indonesia. The samples were selected using quota sampling. Data were analyzed using Pearson correlation test.Results: Results of the Pearson correlation tests between self efficacy and perceived susceptibiliy showed r: 0.191, perceived severity r: 0.239, perceived benefits r: 0.256, perceived barriers r: 0.272, and cues to action r: 229; with all values p<0.05.Conclusion: There was a significant correlation between perceived vulnerability, perceived severity, perceived benefits and perceived barriers, as well as cues to action with self-efficacy in applying the new Model of Assertive Patient-Physician Communication, "CERDAS”.